Killing rage: ending racism - Hooks, Bell (H. Holt and Co, 1995)
Introduction: race talk -- Killing rage: militant resistance -- Beyond black rage: ending racism -- Representations of whiteness in the black imagination -- Refusing to be a victim: accountability and responsibility -- Challenging sexism in black life -- The integrity of black womanhood -- Feminism: it's a black thing -- Revolutionary feminism: an anti-racist agenda -- Teaching resistance: the racial politics of mass media -- Black beauty and black power: internalized racism -- Healing our wounds: liberatory mental health care -- Loving blackness as political resistance -- Black on black pain: class cruelty -- Marketing blackness: class and commodification -- Overcoming white supremacy: a comment -- Beyond black only: bonding beyond race -- Keeping a legacy of shared struggle -- Where is the love: political bonding between black and white women -- Black intellectuals: choosing sides -- Black identity: liberating subjectivity -- Moving from pain to power: black self-determination -- Beloved community: a world without racism